The Subjective Cost of Young Children: A European Comparison - Sonja Spitzer; Angela Greulich; Bernhard Hammer (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
Understanding child-related costs is crucial given their impact on fertility and labour supply decisions. We quantify and compare the cost of children in Europe by analysing the effect of child births on parents' self-reported ability to make ends meet. This study is based on EUSILC longitudinal data for 30 European countries from 2004 to 2015, enabling comparisons between country groups of different welfare regimes. Results show that newborns decrease subjective economic wellbeing in all regions, yet with economies of scale in the number of children. The drop is mainly caused by increased expenses due to the birth of a child (direct costs), which are largest in high-income regions. Immediate labour income losses of mothers (indirect costs) are less important in explaining the decrease. These income losses are closely related to the employment patterns of mothers and are highest in regions where women take extensive parental leave. In the first years after the birth, indirect costs are mostly compensated for via public transfers or increased labour income of fathers, while direct costs of children are not compensated for.
Keywords: 300; Cost of children; subjective economic wellbeing; European welfare states; EU-SILC